2(5c-1)-3=6c+3

Simple and best practice solution for 2(5c-1)-3=6c+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5c-1)-3=6c+3 equation:


Simplifying
2(5c + -1) + -3 = 6c + 3

Reorder the terms:
2(-1 + 5c) + -3 = 6c + 3
(-1 * 2 + 5c * 2) + -3 = 6c + 3
(-2 + 10c) + -3 = 6c + 3

Reorder the terms:
-2 + -3 + 10c = 6c + 3

Combine like terms: -2 + -3 = -5
-5 + 10c = 6c + 3

Reorder the terms:
-5 + 10c = 3 + 6c

Solving
-5 + 10c = 3 + 6c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-6c' to each side of the equation.
-5 + 10c + -6c = 3 + 6c + -6c

Combine like terms: 10c + -6c = 4c
-5 + 4c = 3 + 6c + -6c

Combine like terms: 6c + -6c = 0
-5 + 4c = 3 + 0
-5 + 4c = 3

Add '5' to each side of the equation.
-5 + 5 + 4c = 3 + 5

Combine like terms: -5 + 5 = 0
0 + 4c = 3 + 5
4c = 3 + 5

Combine like terms: 3 + 5 = 8
4c = 8

Divide each side by '4'.
c = 2

Simplifying
c = 2

See similar equations:

| 5x^2-4x-7=1-x | | 3t-6=4(t+7) | | 2x^2+x=10 | | .2y+6=-8 | | -2(t+2)=0 | | 16.546+X=5.5X+X | | 16.546+X=4.333X+X | | 2(x-1)-10=0 | | 0.25y+6=-18 | | 12x^2+8x-15x= | | 38-18=5(x-8) | | 12x^2-8x-15x= | | 2.527X=10+X | | 4x^3+6x^2-6x-4=0 | | 12x^2-8x+15x= | | 19+3y-3=12y-9-4y | | 3x-4(2)=16 | | x+22+4x=-10-4x-13 | | 10x+5x+15= | | -15x-20=-13x+80 | | 4*x+(x+1)*3=24 | | 25-5x=16+4x | | 3y^2-3y-8=0 | | 4x-5=5x+2 | | -11z+56=-10 | | 5p^2-25=4p^3+24 | | 2e-6= | | 3x+12x+6=0 | | 2y-7=3y+4 | | 16x^2=-8x-1 | | -12+2(-2)-9= | | -8(6)+(-7)(-5)= |

Equations solver categories